Coupling between visual information and body sway in adults with Down syndrome - Gomes, Matheus Machado; Moraes, Renato; Barela, Jose Angelo [UNESP] (Elsevier B.V., 2016)
Background: Prior studies suggest that infants with Down syndrome (DS) need more experience to acquire a similar relationship between visual information and body sway than infants without DS. However, it is unclear how adults with DS deal with visual information to control posture. Aim: To examine the coupling between visual information and body sway in adults with DS. Methods: Twenty adults with DS (25.8 +/- 4.0 years) and twenty age- and sex-matched controls (25.6 +/- 4.0 years) stood upright inside a moving room in two experimental conditions: continuous (room oscillated continuously at 0.1,0.2, and 0.5 Hz) and discrete (room moved forward or backward for a brief moment). Tridimensional body sway and moving room displacement data were registered. Results: Individuals with DS coupled their body sway to the imposed visual stimulus, but showed higher position variability at frequencies other than the frequency of room movement (0.48 cm) and lower coherence (0.80) than controls (0.40 cm and 0.90, respectively). Conclusions: Adults with DS were able to couple to the visual cue, but with differences in terms of the scaling of postural responses to spatial parameters of the visual stimulus. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Postural control; Disabilities; Sensory information